2017
DOI: 10.1099/jmm.0.000464
|View full text |Cite
|
Sign up to set email alerts
|

Importance of adhesins in the recurrence of pharyngeal infections caused by Streptococcus pyogenes

Abstract: Recurrence seems not to be associated with biofilm formation. However, pili and fibronectin-binding proteins could be associated with recurrence because FCT-4 isolates which harbour two fibronectin-binding proteins are more frequent among recurrent isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
4
1
Order By: Relevance
“…The only study among these with a sufficient number of emm3 isolates, found a more homogenous distribution of biofilm forming capacity within this emm type compared to our data (Baldassarri et al, 2006). Other studies addressing the relationship between emm type and biofilm formation includes no or just a few emm1, emm3, and/or emm28 isolates (Lembke et al, 2006;Thenmozhi et al, 2011;Wozniak et al, 2017), making a comparison to our results unreliable.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…The only study among these with a sufficient number of emm3 isolates, found a more homogenous distribution of biofilm forming capacity within this emm type compared to our data (Baldassarri et al, 2006). Other studies addressing the relationship between emm type and biofilm formation includes no or just a few emm1, emm3, and/or emm28 isolates (Lembke et al, 2006;Thenmozhi et al, 2011;Wozniak et al, 2017), making a comparison to our results unreliable.…”
Section: Discussioncontrasting
confidence: 86%
“…M protein, encoded by the emm gene, has an important role in S. pyogenes biofilm formation (Cho and Caparon, 2005;Courtney et al, 2009). However, there is conflicting evidence for a potential association between emm type and biofilm formation (Baldassarri et al, 2006;Koller et al, 2010;Ogawa et al, 2011;Wozniak et al, 2017). Other surface associated molecules known to be involved in S. pyogenes biofilm formation include pili (Manetti et al, 2007), streptococcal collagen like protein 1 (Scl1) (Oliver-Kozup et al, 2011) and hyaluronic acid capsule (Cho and Caparon, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For preparation of the infective inoculum, an erythromycin‐resistant S. pyogenes clinical isolate of each M type that had been previously reported was grown in Todd–Hewitt broth at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…However, the frequency of reinfection with FCT-4-type S. pyogenes was high. Since FCT-4-type S. pyogenes possesses two fibronectinbinding proteins, there may be a causal link between bacterial reinfection and adhesion molecules [14]. Moreover, the methods of bacterial genetic analysis were different between these studies and our study.…”
Section: Discussionmentioning
confidence: 66%